Analisis Lemahnya Penegakkan Hukum dari Kausalitas Maraknya Agen Judi Online di Indonesia - Syahir, Fabhian Halky; Raharjo, Angga Sandhika; Nadjima, Aulia Rachmatullah; Irvan, Rafi Muhammad; Viano, Nurloise; Rahman, Hafizh Aulia; Putra Pammuji, Daffa Adam; Hasnakusumah, Raisha Tiara; Marsanthy, Talitha Aqiella; Mulyadi, Mulyadi (Media Hukum Indonesia (MHI), 2024)
Abstract: Gambling is a game that uses money or goods as bets, such as playing dice and cards. Meanwhile, online gambling is gambling conducted online via the internet. According to Article 303 paragraph (3), it is explained that “a game called gambling is any game, where in general the possibility of obtaining profit depends solely on luck, as well as because the player is better trained or more skilled. The method used in this research is qualitative research where this method involves collecting relevant information and data from various reliable sources. To obtain credible sources, the author uses online library tools such as journals, scientific articles, e-books, and websites that have been tested for reliability by testing institutions. In Indonesia, the eradication of online gambling agents is needed to overcome the problem of online gambling addiction and reduce the unemployment rate. Data-box noted that in 2023, around 7.9 million or 5.45% of Indonesian people are still unemployed. The phenomenon of online gambling is triggered by several factors, including the development of information technology that facilitates access to online gambling sites. In addition, ef ective law enforcement and public awareness of the importance of understanding the negative impact